Reading Obama dreams, hope, and the American political tradition - Kloppenberg, James T. (Princeton Princeton University Press, 2011)
Derided by the Right as dangerous and by the Left as spineless, Barack Obama puzzles observers. In Reading Obama, James T. Kloppenberg reveals the sources of Obama's ideas and explains why his principled aversion to absolutes does not fit contemporary partisan categories. Obama's commitments to deliberation and experimentation derive from sustained engagement with American democratic thought. In a new preface, Kloppenberg explains why Obama has stuck with his commitment to compromise in the first three years of his presidency, despite the criticism it has provoked.
Includes bibliographical references (p. [267]-285) and index.
Keywords: Obama, Barack--Philosophy.